SPINAL MAST CELL TUMORS IN DOGS: IMAGING FEATURES AND CLINICAL OUTCOME OF FOUR CASES. Issue 1 (9th October 2016) - Moore, Trevor W.; Bentley, R. Timothy; Moore, Sarah A.; Provencher, Michele; Warry, Emma E.; Kohnken, Rebecca; Heng, Hock Gan
Abstract : Published information regarding canine vertebral column mast cell tumors (MCTs) is limited. The objectives of this study were to report clinical and advanced imaging findings for a group of dogs with confirmed spinal MCT. Inclusion criteria for this retrospective case series were dogs with spinal magnetic resonance imaging (MRI) or computed tomography (CT) scans and a histological diagnosis of spinal MCT. Clinical, imaging, treatment, and outcome data were recorded. Four dogs met inclusion criteria. One dog had primary spinal MCT and three dogs had metastatic spinal MCT. All four dogs presented for paraspinal hyperesthesia and subacute progressive or acute myelopathy. All CT and MRI lesions were extradural. Two cases exhibited distinct masses in the epidural space. In one case, an epidural tumor invaded from the paravertebral musculature. One case exhibited polyostotic lesions indistinguishable from multiple myeloma by MRI. One dog with a primary epidural low‐grade MCT remains clinically normal 4 years postoperatively, following adjunctive lomustine. An epidural high‐grade MCT, metastatic from a cutaneous tumor, recurred within 2 months of surgery despite adjunctive vinblastine. Two high‐grade cases with concurrent visceral involvement were euthanized immediately after imaging. In dogs, MCT should be considered as a differential diagnosis for a progressive painful myelopathy and CT or MRI evidence of an extradural spinal lesion (epidural, paravertebral, or polyostotic). While more often associated with cutaneous or disseminated disease, MCT may also occur as a primary tumor of the epidural space in dogs.